A note on quantizations of Galois extensions - Ilhan, Asli Guclukan (Elsevier Science Bv, 2014)
In Huru and Lychagin (2013), it is conjectured that the quantizations of splitting fields of products of quadratic polynomials, which are obtained by deforming the multiplication, are Clifford type algebras. In this paper, we prove this conjecture. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Categorical quantizations; Galois extensions; Clifford algebras